Original paperTHE ASSOCIATION OF GENE POLYMORPHISMS WITH ATHLETE STATUS IN UKRAINIANS - Drozdovska, S.B.; Dosenko, V.E.; Ahmetov, I.I.; Ilyin, V.N. (Biology of Sport, 2013)
Athletic performance is a polygenic trait influenced by both environmental and genetic factors. Objective: to investigate individually and in combination the association of common gene polymorphisms with athlete status in Ukrainians. Methods: A total of 210 elite Ukrainian athletes (100 endurance-oriented and 110 power-orientated athletes) and 326 controls were genotyped for ACE I/D, HIF1A Pro582Ser, NOS3 –786 T/C, PPARA intron 7 G/C, PPARG Pro12Ala and PPARGC1B Ala203Pro gene polymorphisms, most of which were previously reported to be associated with athlete status or related intermediate phenotypes in different populations. Results: Power-oriented athletes exhibited an increased frequency of the HIF1A Ser (16.1 vs. 9.4%, P = 0.034) and NOS3 T alleles (78.3 vs. 66.2%, P = 0.0019) in comparison with controls. Additionally, we found that the frequency of the PPARG Ala allele was significantly higher in power-oriented athletes compared with the endurance-oriented athletes (24.7 vs. 13.5%; P = 0.0076). Next, we determined the total genotype score (TGS, from the accumulated combination of the three polymorphisms, with a maximum value of 100 for the theoretically optimal polygenic score) in athletes and controls. The mean TGS was significantly higher in power-oriented athletes (39.1 ± 2.3 vs. 32.6 ± 1.5; P = 0.0142) than in controls. Conclusions: We found that the HIF1A Ser, NOS3 T and PPARG Ala alleles were associated with power athlete status in Ukrainians.